P121 Comparison of Actigraphy versus PSG and Perception of Sleep in Patients with Excessive Daytime Sleepiness. (7th October 2021) - Roebuck, T; McDermott, E; Cuesta, R; Nguy, R; Spiteri, M; van Braak, E; Ho, S; Davies, S
Abstract: Actigraphy is used as a validated measure of rest and sleep, however, there are reported differences in WASO in healthy individuals (Chinoy, 2021). Methods: This study compares the sleep parameters from PSG with simultaneous overnight actigraphy on patients the night prior to MSLT. We also compare the actigraphy data collected on the week prior to the PSG with the patient's sleep diary. 22 subjects, age 38.7 ± 3.1 years, BMI 23.5 ± 1.4 kg/m2, 40.1% male, 4 participants were treated with CPAP. Results: WASO was found to be under estimated by actigraphy versus PSG (y=-0.957x+18.014, R2=0.51), there is an increase in underestimation beyond 18minutes. Our data also show on overestimation of sleep onset latency by actigraphy versus PSG when sleep latency is longer than 12 minutes (y=0.27x-12.04, R2=0.08). Total sleep time was perceived to be longer on the PSG night than the PSG data shows (y=0.68x-4.65, R2=0.21). Data demonstrated participants to overestimate their sleep period in their sleep diary compared to the actigraphy data (y=-0.87x+6.58, R2=0.21). T-tests showed a significant difference between WASO (minutes) detected by PSG and the actigraphy data (67.4 ± 8.9 vs 33.3 ± 3.9 p=0.0007). There were no other significant differences in the datasets. Conclusion: Actigraphy uses activity data and light detection to estimate rest and sleep periods in wearers. Our data reflects expected differences reported in the literature of actigraphy data versus PSG due to the limitation of actigraphy being able to differentiate between sleep and motionless wakefulness.